Dynamics of Informal Settlement Expansion on the Urban Fringe: The Case of Birbir Town, Southern Ethiopia - Hantalo, Arba Haniche; Dube, Engida Esayas (Alanya Üniversitesi, 2023)
This study examines the dynamics of fringe land invasion in Birbir Town, southern Ethiopia by adopting a descriptive survey design with both qualitative and quantitative data analyses. Primary data were acquired through a household survey, key informant interviews, focus group discussions, and observations. This study also benefited from relevant secondary sources. Using a simple random sampling technique, 156 household heads were selected from Birbir and two adjacent rural areas. The study revealed that informal settlement expansion in the form of fringe land invasion occurs in Birbir Town predominantly due to population increase, urban sprawl, migration, poor land administration and governance systems, a lack of boundary demarcation, and the presence of available unserviced public land near the town. The process was intensified by actors such as farmers, local administrators, informal dealers, politicians, and local elders. The encroachment of urban fringe areas has led to deforestation, relinquishment of cultivable acreage, entitlement disputes, a prevailing trend of illicit land occupation, an unstructured urban expansion pattern, and a surge in criminality, fostering discordant communities. This study contributes to the understanding of informality on the urban fringe as posing socioeconomic and governance challenges in small towns of developing countries by presenting the case of Birbir.